Patterns and Strategies of Responses to Compliments: A Case Study on Post-graduate Students of One State University in Indonesia - Handayani, Sri (ENGLISH JOURNAL, 2016)
This study investigated responses to compliments of male and female Indonesian second semester post-graduate students in Indonesian cultural setting. The study focussed on patterns and strategies of responses commonly used by the post-graduate students in informal situation speech acts. The graduate students of English Department from three classes who participated in this study were randomly selected and given compliments in natural settings. The data were analyzed by using patterns and strategies of responses to the compliments proposed by Farghal and Al-Khatib (2001). The patterns of responses were classified into some terms: (1) simple responses vs. complex responses; (2) macro-functions vs. micro-illocutions; and (3) intrinsically-complex responses vs. extrinsically-complex responses. Meanwhile, the strategies of responses were categorized into terms like accepting/agreeing and down grading or rejecting/disagreeing. The formula of compliments used to collect data was directed to address some good possessions which were positively valued by the students and considered to be the most common formula in Indonesia. The results of study showed that: (1) male tended to be more frequent to use simple responses than that of female who tended to use complex compliments in responding to the compliments; (2) male tended to reject the compliments by doubting and denying strategies, meanwhile, female tended to accept the compliments by confirming and tagging strategies; and (3) male tended to reject compliments, however, accept some compliments by using simple and non-verbal responses.